Réponses cardiorespiratoires lors d`une évaluation musculaire isocinétique du tronc - Bernuz, B.; Edouard, P.; Coudeyre, E.; Calmels, P.; Bedu, M.; Roche, F.; Degache, F. (Science & Sports, 2012)
Objective To assess cardiorespiratory stress of isokinetic trunk extensor and flexor. Method Eight male subjects (24.9 ± 1.4 years) performed extension and flexion exercises isokinetic dynamometer. This test consisted of three repetitions at 30°/s, three repetitions at 60°/s and 15 repetitions at 120°/s in concentric mode. Two minutes of recovery were observed between each series. Measures of heart rate, blood pressure, oxygen consumption and blood lactate were performed at rest and at the end of each series. Results A significant increase of 84% HR max, corresponding to 80% of theoretical maximum heart rate was measured. The elevation of systolic BP during exercise corresponded to a 20% increase compared to the rest. An increase of 47% of VO2max was measured. The peak of lactate observed during a series of 15 repetitions, showed a significant increase of 230% over the resting value. The search for cardiovascular risk factors must be made before any isokinetic test. A conventional incremental exercise test may be offered to patients at risk if a number corresponding to a test of fatigue is being considered.